Development of a numerical simulation technique for modeling of failure of structures with stress concentrator under dynamic loading - Iziumova, A.Yu.; Kostina, A.A.; Panteleev, I.A.; Vedernikova, A.I.; Prokhorov, A.E.; Vshivkov, A.N. (Perm Federal Research Centre Journal, 2020)
The constitutive equations taking into account non-local character of fracture near stress concentrators under dynamic loading have been developed. The generalization of a critical distance theory for dynamic loading which can be used for the fracture prediction in the wide range of strain rates (10-3to 104c-1) has been suggested. The analysis of inelastic deformation near the stress concentrators has been carried out in order to increase the accuracy of fracture prediction. Based on modeling damage accumulation processes, the mechanism of formation of critical distance in the stress concentrators area as a result of development of dissipative structure in ensemble of defects has been offered. Investigation on fracture surface of metallic specimens has been carried out. It has been shown that there are two areas with different macrorelief; characteristic size of the transition zone correlates with the critical distance value.